2015
DOI: 10.1002/lt.24160
|View full text |Cite
|
Sign up to set email alerts
|

Declining liver graft quality threatens the future of liver transplantation in the United States

Abstract: National liver transplantation (LT) volume has declined since 2006, in part because of worsening donor organ quality. Trends that degrade organ quality are expected to continue over the next 2 decades. We used the United Network for Organ Sharing (UNOS) database to inform a 20-year discrete event simulation estimating LT volume from 2010 to 2030. Data to inform the model were obtained from deceased organ donors between 2000 and 2009. If donor liver utilization practices remain constant, utilization will fall f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 47 publications
(65 reference statements)
2
101
0
Order By: Relevance
“…These issues have been raised previously,(6) but deserve updated emphasis as healthcare costs continue to spiral upwards. For example, complicated variceal bleeding may increase, which would lead to high hospitalization costs of $28 513 per patient in 2015 US dollars (adjusted for inflation from 2008 US dollars using the Consumer Price Index Medical Care component for all US cities).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These issues have been raised previously,(6) but deserve updated emphasis as healthcare costs continue to spiral upwards. For example, complicated variceal bleeding may increase, which would lead to high hospitalization costs of $28 513 per patient in 2015 US dollars (adjusted for inflation from 2008 US dollars using the Consumer Price Index Medical Care component for all US cities).…”
Section: Discussionmentioning
confidence: 88%
“…(5) The recent decline in LT may be a harbinger of further reductions in LT in the coming years. (6) Such a decline in transplant availability would place a greater burden on centers managing ESLD patients on the waitlist.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason for which every possible deceased donor is thoroughly evaluated by organ procurement associations and transplant physicians. A variety of algorithms have been implemented in order to assess the risk of graft failure after liver transplantation [13] in an attempt to better match grafts and recipients. One of these scores -the donor risk index [4], used in our study, is being extensively used by centers worldwide and incorporates variables regarding the physical status of the patient, the cause of cerebral death, organ allocation and cold ischemic time.…”
Section: Discussionmentioning
confidence: 99%
“…Orman et al [13] published a study where they analyzed the impact of donor organs by the year 2030 considering the actual trend. They found that the use will fall from 78% to 44% by 2030, resulting in 2230 fewer LTs.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for liver transplantation, like other organs, continues to rise with no corresponding rise in supply-with the obesity epidemic projected to decrease the available pool of donor organs [28,29]. Liver tissue engineering seeks to overcome these issues by creating functional, viable, and biocompatible hepatic tissue for those with ESLD [30].…”
Section: Livermentioning
confidence: 99%